Report of deputation of the Finance and General Purposes Comittee to Lord Halifax, Foreign Secretary, April 6, 1938 - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959.; Elvin, Herbert Henry
1938-04-07 017a-0075-001 292/946/17a/74